2019
DOI: 10.1519/jpt.0000000000000182
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Task Performance: Influence of Frailty, Level of Physical Activity, and Cognition

Abstract: Frail older adults presented worse performance in the TUG when compared with nonfrail older adults. The dual-task test does not differentiate older adults with frailty syndrome, regardless of cognitive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
8
0
2
Order By: Relevance
“…Other terms in the literature to denote gait speed at usual pace included comfortable, habitual, normal, or preferred. Six studies recorded gait speed also during dual task 36,51,59,110,112 . Overall, the 4 m walk is the most used version for studies in older people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other terms in the literature to denote gait speed at usual pace included comfortable, habitual, normal, or preferred. Six studies recorded gait speed also during dual task 36,51,59,110,112 . Overall, the 4 m walk is the most used version for studies in older people.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies recorded gait speed also during dual task. 36,51,59,110,112 Overall, the 4 m walk is the most used version for studies in older people.…”
Section: Heterogeneitymentioning
confidence: 99%
“…TPA, activity counts, postural transitions, and EE were studied too infrequently (<5 times) to synthesise individual albatross plots and standardised regression coefficients. TPA was studied in one population [48], activity counts were studied in three populations [40,48,62], postural transitions were studied in one population [63], and EE was studied in three populations [62,39,56], with higher measures corresponding with lower frailty in all analyses.…”
Section: Associations Between Physical Activity Sedentary Behaviour and Frailtymentioning
confidence: 99%
“…outlines the measurement and characteristics of PA/SB and frailty. PA/SB measures included light physical activity (LPA)[44,42,49,45,37,62,46,50,52], moderate-to-vigorous physical activity (MVPA)[36,44,53,50,52,49,45,37,56,62,46], step count[49,45,47,48,62,46,50,54,51,55,56], accelerometer activity counts[40,48,62], total physical activity (TPA)[48], postural transitions (TRS)[63], energy expenditure (EE)[39,62,56], sedentary behaviour (SB)[36,44,43,38,45,37,62,46,52,…”
mentioning
confidence: 99%
“…This test has been used not only to assess the risk of falls in the elderly due to sarcopenia, but also to evaluate physical function in previous studies with participants who had cerebral palsy, stroke, and Parkinson's disease [11][12][13]. In addition, some studies were conducted with a focus on children and adolescents [13,14], and another study has shown that TUG performance is associated with the level of physical activity [15]. Therefore, we believe that TUG is useful for evaluating the physical function of healthy adults.…”
Section: Introductionmentioning
confidence: 99%